THE EFFECTS OF WATER FRACTION OF BITTER MELON (MOMORDICA CHARANTIA) LEAF EXTRACT IN MAMMARY GLAND DEVELOPMENT OF BALB/C MICE (MUS MUSCULUS) WITH HISTOLOGICAL AND MOLECULAR BIOLOGICAL ANALYSIS OF PROTEIN APPROACHES - Nur Hayati; Afifah Nur Aini; Nafisatuzzamrudah Nafisatuzzamrudah; Umie Lestari (UPT Penerbitan Universitas Jember, 2016)
Recently many breast-feeding mothers use chemical drugs to ease milk secretion, while the said drug could cause side effects if consumed in a long time. The problem could be solved by using natural medicine like bitter melon leaf because it contains charantin which is characteristically identical to phytosterol [6]. This study aimed to discover the potention of water fraction of bitter melon leaf extract to stimulate mammary gland development in Balb/c mice. The development of mammary gland was observed through histological approach by calculating the number of cells in mammary gland, and through molecular biological analysis of protein approach by using SDS-PAGE. The histology of mammary gland showed that the administration of the extract with concentration of 11,200 ppm had the highest number of cells, followed by 5,600 ppm; 22,400 ppm and 16,800 ppm. The result of SDS-PAGE on isolated mammary gland protein showed that the molecular weight of the proteins in the controlled treatment were 2, 5, 8, 10, 12, 19, 34, 40 and 49 kDa. In treatment with concentration of 5,600 ppm there were only 10, 12, 34, 40 and 49 kDa. In treatment with concentration of 11,200 ppm there were similar kinds of proteins with the controlled treatment, only without the 8 kDa protein. In treatment with concentration of 16,800 and 22,400 ppm, there were only 2, 5, 10, 12 kDa. The conclusion of this study was water fraction of bitter melon leaf extract could affect the development of mammary gland in Balb/c mice.